2016
DOI: 10.3389/fnins.2016.00580
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Provides Neuroprotection in Model of Traumatic Brain Injury via the Nrf2–ARE Pathway

Abstract: The neuroprotective effect of sinomenine (SIN) has been demonstrated in several brain injury models. However, its role and molecular mechanism in traumatic brain injury (TBI) remain unknown. In this study, we investigated the neuroprotective effects of SIN in the weight-drop model of TBI in male ICR mice. Mice were randomly divided into the sham and TBI groups, SIN (10 mg/kg, 30 mg/kg and 50 mg/kg, administered intraperitoneally) or equal volume of vehicle was given at 30 min after TBI. Treatment with 30 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Recent studies indicated that SIN has anti-cancer effects on several cancers, such as breast cancer, hepatocellular carcinoma, and lung cancer [ 12 , 13 , 17 ]. Evidence also confirmed the neuroprotective effects of SIN [ 11 , 18 , 19 ]. Furthermore, a growing number of studies have revealed that SIN has multiple pharmacological activities, including antiangiogenic, antirheumatic, immunosuppressive effects, and anti-inflammatory effects [ 11 ].…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies indicated that SIN has anti-cancer effects on several cancers, such as breast cancer, hepatocellular carcinoma, and lung cancer [ 12 , 13 , 17 ]. Evidence also confirmed the neuroprotective effects of SIN [ 11 , 18 , 19 ]. Furthermore, a growing number of studies have revealed that SIN has multiple pharmacological activities, including antiangiogenic, antirheumatic, immunosuppressive effects, and anti-inflammatory effects [ 11 ].…”
Section: Discussionmentioning
confidence: 71%
“…In oxidative stress, production of free radicals enhanced that result in oxidation and nitration of proteins, lipid peroxidation and DNA damage [5]. In TBI, the level of MDA is reported to be enhanced and activity of GPx and SOD reduced in the neuronal tissues [17]. Data of the study reveal that treatment with vorinostat reduces the altered parameters of oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“… 7 , 8 SIN exerts neuroprotective effects in different central nervous system (CNS) diseases, including cerebral ischemia, intracerebral hemorrhage, and neurodegenerative diseases. 9 , 10 However, the mechanisms of these effects are still not well understood. Besides, few studies have addressed the neuroprotective effect of SIN in TBI.…”
Section: Introductionmentioning
confidence: 99%